PENGARUH PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY DAN UKURAN PERUSAHAAN TERHADAP PROFITABILITAS - Sriviana, Eva (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2013)
The purpose of this research is to disclosure the Corporate Social Responsibility and the sizeof the company which can influence the companyâs profitability. The samples in this research are themanufacturer companies which are listed in Indonesia Stock Exchange (IDX) for more than 3 years ofobservation within the of period 2009-2011. The total samples in this research are 31 companies whichare taken by using the purposive sampling. The data analysis is using multiple regression analysis.The analysis technique uses F statistic test which shows that all the independent variables and tstatistic test shows how far is one variable which inserted in the model have an influence together tothe dependent variables and t statistic test shows that how far is one independent variable individuallyexplains the variation of dependent variable with the significant level of 5%. The result of this researchshows that simoultanouesly CSR and the company size has a signifcant influence to the companyâsprofitability. Partially CSR has a significant influence to the profitability while the company size has asignificant influence to the profitability.Keywords: corporate social responsibility (CSR), company size, profitability.